Kajian Historis: Corak Sastra Arab (Zaman Jahiliyah, Shadr Islam dan Umawiyah) - A. Tjalau, Cutri; Safii, Randi (Assuthur: Jurnal Pendidikan Bahasa Arab, 2023)
Abstract: This paper aims to examine the style of Arabic literature during the time of Jahiliyah, Shadr Islam (the beginning of Islam) and Umawiyah. The method used in this study is the analytical descriptive method, namely by describing how the form or pattern of Arabic literature during the time of Jahiliyah, Shadr Islam (the beginning of Islam) and Umawiyah. While the approach applied in this study is a historical approach, where researchers look for histories related to the style of Arabic literature during the Jahiliyah, Shadr Islam (the beginning of Islam) and Umawiyah. The results of this research are 1) in the Jahiliyah era, the style of Prose and Poetry in this era is almost the same, starting from the lafadznya which is clear and eloquent, has a deep meaning, rhymes. Prose at this time also consisted of Sermons, Testaments, Matsals, Hikmah, and Qissoh. 2) Shadr Islam In this age Prose and Poetry also developed, but Prose was much more developed than poetry. Especially in the Khutbah, this is because at this time the Khutbah is used to ignite the spirit of the warriors to fight to spread Islam. While poetry has not developed enough, this is because poets at this time are busy fighting and studying the Qur'an and hadith. So, in terms of meaning, imagination, lafadz, and language style do not achieve high dignity. Prose at this time included the Khutbah, Matsal, and Kitabah. 3) The Age of the Umayyad Dynasty, in this age Prose and Poetry are much developed rapidly compared to the previous two eras. This development was due to the emergence of political parties so that many sermons and poems developed to support their respective parties, and this became a source of income for poets. However, at this time poetry had begun to deviate from its original purpose of spreading Islam using good language, but after the establishment of the Umayyads they used the politics of violence and deceit which made it compulsory to buy oral poets. Prose at this time included the Khutbah, Rasail, and Kitabah which in terms of language imitated and decorated from the language style of the Qur'an which was smooth, clear, and had a deep meaning.